The effect of travel time to school to academic knowledge of primary school students in the Philippines - Itulid, Jayrald; Malig, Ivan
In this paper, the researchers discuss the effect of travel time to school to academic knowledge using the Cebu Longitudinal Health and Nutrition Survey. The survey includes Filipino women in Cebu who gave birth between the dates of May 1, 1983 and April 30, 1984, and includes follow-up surveys for the children given birth. The follow-up surveys in 1994 are used as the main drivers for the paper’s regression, where the children are either 10 or 11 years old at the time. Four different standardized tests are used as proxies for academic knowledge: (1) Cebu reading (2) mathematics, (3) English, and (4) non-verbal achievement tests. A multiple linear regression is used to estimate the effect of travel time to school to these four test scores. The results show statistically significant negative linear relationships between travel time and the scores that the children got from the tests conducted.